The transforming network of a foreign company operating in Mongolia. Case: A Finnish firm in Mongolia - Jokinen, Kiia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2015)
In the globalising business environment ever fewer market areas remain unknown. Mongolia is yet only considered as an isolated strip between two power states. The purpose of this study is to put Mongolia on the map of academic business research. This is done by describing the transforming network of a foreign company operating in Mongolia. The objective of the study is approached through a case study, which presents the transformation of a Finnish company operating in Mongolia. This study aims at providing understanding on how the foreign case company observes the transformations of its network. The transformation within the case company is reflected to the transformations that occur in the Mongolian business environment. This study was conducted through a qualitative, intrinsic case study approach. The empirical data was gathered by using the method of network pictures. The network pictures were completed with the assistance of themed interviews. In order to be able to analyse the transformation within a network, three different time periods were observed: the past period around 2000, the present around 2014, and the estimated future around 2020. The data was collected from four executives positioned either in Finland, Russia or Mongolia. The respondents have a long experience within the case company, they hold managerial position, and therefore were able to offer valuable data for this study. The analytical framework used to analyse the collected data was built on the industrial network model, the ARA (actors-resources-activities)-model. The study shows that the changing business environment of Mongolia was utilised by the case company. In order to better meet the transforming customer wishes, the case company transformed from being a retailer to being a manufacturer. The case company was able to become a pioneer in the market. Thus, the case company has undergone similar kind of rapid transformation as the economy of Mongolia in entirety. This study shows that the general nature of the ARA-model makes it usable for new research contexts. The initial ARA-model offers a way to identify the dimensions of a network and a mean to understand these dimensions. The ARA-model can be applied to different contexts and to all time dimensions, past, present and future. The managerial recommendations offered in this study are directed towards the managers that plan to start operations in Mongolia. While this study is the first of its kind, it offers a good starting point for the future research on the change of Mongolian business networks. Valuable information could, for example, be obtained from a comparative study between the case company of this study and a multinational mining company operating in Mongolia.